2022
DOI: 10.1186/s13054-022-03979-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma disappearance rate of albumin when infused as a 20% solution

Abstract: Background The transcapillary leakage of albumin is increased by inflammation and major surgery, but whether exogenous albumin also disappears faster is unclear. Methods An intravenous infusion of 3 mL/kg of 20% albumin was given over 30 min to 70 subjects consisting of 15 healthy volunteers, 15 post-burn patients, 15 patients who underwent surgery with minor bleeding, 10 who underwent surgery with major bleeding (mean, 1.1 L) and 15 postoperative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Various clinical studies examine the effects of albumin in the clinical context. Zdolsek et al have shed light on the impact of exogenous albumin administration on fluid dynamics under various clinical conditions [ 196 ]. The primary focus of their study was to evaluate the rate at which infused albumin dissipates from the bloodstream, quantified as the half-life ( T 1/2 ), under different clinical scenarios.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Various clinical studies examine the effects of albumin in the clinical context. Zdolsek et al have shed light on the impact of exogenous albumin administration on fluid dynamics under various clinical conditions [ 196 ]. The primary focus of their study was to evaluate the rate at which infused albumin dissipates from the bloodstream, quantified as the half-life ( T 1/2 ), under different clinical scenarios.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…If the glycocalyx functions as a permeability barrier, the intravascular half-life of exogenous albumin contained in an infusion of 20% albumin would be expected to be shortened by surgery and inflammation. However, postoperative patients and post-burn patients with moderately severe inflammation (plasma C-reactive protein of 60–80 mg/L) and patients undergoing surgery with minor hemorrhage had the same intravascular half-life of exogenous albumin when compared with healthy volunteers [ 55 ]. The post-burn patients given 20% albumin even showed a normal capillary leakage of albumin and fluid despite major elevations, even up to 100-fold, of plasma syndecan-1 [ 56 ].…”
Section: Glycocalyx and Capillary Permeability In Humansmentioning
confidence: 99%
“…The use albumin as biomarker of capillary leakage is prone to errors in complex clinical situations [55], but a large body of evidence supports that both glycocalyx degradation products [59] and capillary leakage of albumin and fluid [60,61] are increased in septic patients. Fleck et al even reported quadrupled capillary leakage rates in patients with septic shock [62].…”
Section: Glycocalyx and Capillary Permeability In Humansmentioning
confidence: 99%
“…Based on fluid kinetic studies of human patients during surgery, there was a poor correlation between fluid kinetic parameters indicative of increased capillary permeability (escape rate of albumin), with plasma concentrations of inflammatory markers or glycocalyx constituents. 4–7 These observations suggest that changes in capillary permeability are unlikely to account for the magnitude of altered fluid distribution that was observed. Therefore, other factors must contribute to the increase in interstitial fluid during anesthesia.…”
mentioning
confidence: 94%